Evaluation of risk factors for severe apical root resorption in the maxillary incisors following fixed orthodontic treatment - (:unkn) unknown (My University, 2022)
Objective: The aim of this study was to retrospectively determine the prevalence of severe external root resorption in maxillary incisors during fixed orthodontic treatment and to evaluate the possible predisposing factors. Methods: The treatment records of 7000 patients who had been treated between 1990 and 2019 at the Department of Orthodontics Faculty of Dentistry Marmara University were examined, and a total of 120 patients with severe root resorption in at least one of their upper incisors were identified. The following data were retrieved from the patients' records and radiographs: gender, root morphology, overjet, overbite, treatment modality (extraction, non-extraction), treatment duration, buccal and palatal alveolar bone thickness for the maxillary incisors, and amount of movement of the incisal root apices and incisal edges. These data from a group of 90 patients with severe root resorption were compared with the data from a control group of 90 patients with minimal root resorption. The Chisquare test, the Mann–Whitney U-test, and the independent t-test were used for statistical analysis. Results: The prevalence of severe external root resorption was 3.23%, and the results demonstrated significant difference between the groups for the variables of treatment modality (extractions), treatment duration, thickness of the alveolar bone, and amount of incisor movement at the end of the treatment. Conclusion: It can be concluded that extractions, increased treatment duration, thin alveolar bone, and excessive incisor movement represent risk factors for severe root resorption in maxillary incisors following orthodontic treatment
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; external root resorption; maxillary incisors; root morphology; bone thickness; INTRUSION; GROWTH; Orthodontics; external root resorption; maxillary incisors; root morphology; bone thickness